2020
DOI: 10.1002/bit.27342
|View full text |Cite
|
Sign up to set email alerts
|

Stratified microbial structure and activity within anode biofilm during electrochemically assisted brewery wastewater treatment

Abstract: In a bioelectrochemical system (BES), microbial community of anode biofilm is crucial to BES performance. In this study, the stratified pattern of community structure and activity of an anode‐respiring biofilm in a BES fueled with brewery wastewater was investigated over time. The anode biofilm exhibited a superior performance in the removal of ethanol to that of an open‐circuit system. The electrical current density reached a high level of 0.55mA/cm2 with a Coulombic efficiency of 71.4%, but decreased to 0.18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Notably, imaging of biofilm dimensions and correlating this with measured current densities can give valuable information. Hence, fluorescence microscopy as well as optical coherence tomography (OCT) studies were conducted with mixed environmental inocula and in bioelectrochemical flow cell systems of varying formats [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. In several of these studies, model presumptions were corroborated suggesting that the formation of proton gradients from anode to bulk phase will limit biofilm activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, imaging of biofilm dimensions and correlating this with measured current densities can give valuable information. Hence, fluorescence microscopy as well as optical coherence tomography (OCT) studies were conducted with mixed environmental inocula and in bioelectrochemical flow cell systems of varying formats [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. In several of these studies, model presumptions were corroborated suggesting that the formation of proton gradients from anode to bulk phase will limit biofilm activity.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to biological activity in different biofilm depths, there is so far no clear result within past research. While some studies revealed a live outer layer with a dead zone close to the anode [ 28 , 34 , 35 ] others reported the opposite [ 26 , 29 , 33 , 37 ]. Another recent analysis using a flow cell and an environmental inoculum suggested that most metabolic activity would be in the center of 42.5–60 μm thick anode biofilms [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] It is essential to develop functional materials and straightforward approaches to obtain freshwater from seawater and wastewater. [3,4] While conventional electrospinning. [36] The Janus absorber demonstrated a conversion efficiency of 72% and a stable water output of 1.3 kg m -2 h -1 over 16 days under one-sun irradiation without salt deposition.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] It is essential to develop functional materials and straightforward approaches to obtain freshwater from seawater and wastewater. [ 3,4 ] While conventional methods of seawater desalination and wastewater treatment, such as reverse osmosis (RO) [ 5,6 ] and thermal desalination technologies, [ 4,7 ] not only need high technical requirements but also unavoidably cause the large consumption of fossil energy. In recent years, solar‐driven interfacial evaporation technology has aroused much attention due to its advantages of eco‐friendly features and low level of infrastructure.…”
Section: Introductionmentioning
confidence: 99%